Penerapan Strategi Manajemen Pengetahuan untuk Meningkatkan Kinerja Institusi Pendidikan dalam Menghadapi Revolusi Industri 4.0 - Mohammad Kurniadi Rasyid; Agus Rahayu; Lili Adi Wibowo (University of Merdeka Malang, 2021)
The purpose of this study was to find out the effect of implementing knowledge management strategies on the performance of educational institutions in the face of the industrial revolution 4.0. The approach used in this research is a quantitative approach. The sample used in this study is the academic community in one of the private universities in Serpong. The data analysis technique used in the study was Partial Least Square Structural Equation Modeling (PLS-SEM). The results showed that the application of knowledge management strategies was proven to significantly affect the performance of educational institutions. Knowledge management strategies have also been shown to have a strong influence in improving human relations among students. Relationships among humans can be a mediating variable for the relationship between knowledge management strategies and educational institution performance and have the same influence as the direct influence of knowledge management strategies on the performance of educational institutions.